STUDY OF DRAINAGE SYSTEM PLANNING OF JALAN SIDODADI SUBDISTRICT SANGATTA UTARA KUTAI TIMUR REGENCY - SAD, IRY (KURVA S JURNAL MAHASISWA, 2017)
Subdistrit Sangatta Utara, especially on Jl. Sidodadi is an area that is still flooded this is known based on actual circumstances actual in the field when entering the rainy season there is flooding at some point. This thesis aims to determine the existing channel discharge, calculate the debit of the plan flow with a 10 year re-timing, and calculate the drainage capacity (channel dimension) that can accommodate 10 year flood discharge plan. Limitations of the problems reviewed from the writing of this thesis is to analyze the rainfall plan, intensity of precipitation and concentration time, discharge planning analysis and capacity analysis drainage.The research method used is the method of data collection and analysis. The collection of primary data and secondary data, is the first step in this research. Then analyzed by Frequency Analysis method. This method analyzes two types of distributions: Log Person III distribution and Gumbel distributionThe value of rainfall used for the calculation of rainfall intensity is the value of rainfall Log Person Distribution III repeat period of 10 years. For rainfall intensity use Mononobe formula, and calculate drainage channel capacity (channel dimension) for 10 years prediction.The results of this study indicate that the flood that occurred due to drainage system that is not functioning properly. Due to the lack of channels and cleanliness of the channel is very bad and also not united all the parties involved in maintaining and maintaining the cleanliness of drainage. There are also some dimensions of the channel that are not sufficient to accommodate the flood discharge so it needs to be widening and deepening and re-planning of drainage network system Jl. Sidodadi Desa Sangatta Utara to produce a sustainable drainage system.